ChemInform Abstract: Mild and Site‐Selective Allylation of Enol Carbamates with Allylic Carbonates under Rhodium Catalysis. Issue 31 (14th July 2016) - Sharma, Satyasheel; Han, Sang Hoon; Oh, Yongguk; Mishra, Neeraj Kumar; Han, Sangil; Kwak, Jong Hwan; Lee, Seok‐Yong; Jung, Young Hoon; Kim, In Su
Abstract: gives various allylic alcohols and terminal allylated products